A Roadmap to Gene Discoveries and Novel Therapies in Monogenic Low and High Bone Mass Disorders - Formosa, Melissa M.; Bergen, Dylan J. M.; Gregson, Celia L.; Maurizi, Antonio; Kämpe, Anders; Garcia-Giralt, Natalia; Zhou, Wei; Grinberg, Daniel; Ovejero Crespo, Diana; Zillikens, M. Carola; Williams, Graham R.; Bassett, J. H. Duncan; et al. (Frontiers in Endocrinology, 2021)
Genetic disorders of the skeleton encompass a diverse group of bone diseases differing in clinical characteristics, severity, incidence and molecular etiology. Of particular interest are the monogenic rare bone mass disorders, with the underlying genetic defect contributing to either low or high bone mass phenotype. Extensive, deep phenotyping coupled with high-throughput, cost-effective genotyping is crucial in the characterization and diagnosis of affected individuals. Massive parallel sequencing efforts have been instrumental in the discovery of novel causal genes that merit functional validation using in vitro and ex vivo cell-based techniques, and in vivo models, mainly mice and zebrafish. These translational models also serve as an excellent platform for therapeutic discovery, bridging the gap between basic science research and the clinic. Altogether, genetic studies of monogenic rare bone mass disorders have broadened our knowledge on molecular signaling pathways coordinating bone development and metabolism, disease inheritance patterns, development of new and improved bone biomarkers, and identification of novel drug targets. In this review, we describe the monogenic forms of rare low and high rare bone mass disorders known to date, provide a roadmap to unravel the genetic determinants of monogenic rare bone mass disorders using proper phenotyping and genotyping methods, and describe different genetic validation approaches paving the way for future treatments.